Q: A3 - b3 equals

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

A3+b3

a3*b3 = a3b3

(a+b)3=a3+b3+3ab(a+b) a3+b3=(a+b)3-3ab(a+b) a3+b3=(a+b)(a2-ab+b2)

(a -b) · (a2+ab+b2) = (a3+a2b+ab2) - (a2b+ab2+b3) = a3 -b3 (a+b) · (a2 -ab+b2) = (a3 -a2b+ab2) +(a2b -ab2+b3) = a3+b3 More generally: (a ∓ b) · (an-1 ±an-2b +an-3b2 ±an-4b3 +±...+a(±b)n-2 +(±b)n-1) = an ± bn. The mixed terms cancel out themselves.

let binomial be (a + b)now (a+b)3 will be (a+b)(a+b)2 = (a+b)(a2 + 2ab+ b2) = a(a2+ 2ab+ b2) + b(a2 + 2ab+ b2) = a3+ 2a2b+ ab2 + a2b + 2ab2 + b3 = a3+ 2a2b+ ab2 + a2b + 2ab2 + b3 = a3 +3a2b + 3ab2 +b3 hope it helped... :D

Related questions

A3+b3

a3*b3 = a3b3

There are no whole solutions

(a+b)3=a3+b3+3ab(a+b) a3+b3=(a+b)3-3ab(a+b) a3+b3=(a+b)(a2-ab+b2)

0

0

The plus sign. + To add values in the cells A3 and B3 you would do the following: =A3+B3

Go to cell D3 and enter the following: "=A3*B3"

a3 + b3 = (a + b)(a2 - ab + b2) a3 - b3 = (a - b)(a2 + ab + b2

a3 + b3 = (a + b)(a2 - ab + b2) a3 - b3 = (a - b)(a2 + ab + b2)

a3 - b3 = (a - b)(a2 + ab + b2) a3 + b3 = (a + b)(a2 - ab + b2)

a3 + b3 = (a + b)(a2 - ab + b2) a3 - b3 = (a - b)(a2 + ab + b2)